PENYERAPAN FERRO SULFAS YANG DIMINUM BERSAMAAN DENGAN MENU MAKANAN POKOK BERAS, JAGUNG SERTA SINGKONG DENGAN VITAMIN C ATAU PEPAYA: SUATU UJI PENYERAPAN SECARA IN-VITRO - Almasyhuri Almasyhuri; M. Saidin; Sukati Sukati (Persagi, 1998)
Iron tablets containing ferrous sulphate have long been used for the control of iron deficiency anaemia, but the prevalence of anaemia especially among pregnant women is still high. Iron tablets are usually consumed before or after meal. The composition of the meal may affect iron absorption from iron tablets. The objective of this study was to find out the amount of iron absorbed from iron tablets consumed with rice, maize or cassava suplemented with vitamin C or papaya. The results of this study showed that iron absorption is higher if iron tablet is consumed before meal. Vitamin C and papaya increase iron absorption by 10%. Keywords: ferrous sulphate, vitamin C, papaya, iron absorption.